Effect of The Ratio of Purple Sweet Potato Flour and Rice Crust Flour on The Physical, Chemical, and Sensory Properties of High-Fiber Snack Bar - Safira, Tsaania Miftakhul; Yanti, Rini; Manikharda, Manikharda; Triwitono, Priyanto (Indonesian Association of Food Technologists, 2024)
Dietary fiber, an indigestible component of plants, offers significant health benefits for humans. Creating a high-fiber snack bar can be a substitute for meeting daily requirements for dietary fiber. This research aimed to create snack bar products utilizing locally sourced ingredients, specifically rice crust flour and purple sweet potato flour, with the goal of optimizing the utilization of local food resources and enhancing the diversity of Indonesian cuisine. This study aimed to investigate how the proportion of purple sweet potato flour and rice crust flour influenced the chemical, physical, and sensory characteristics of the high-fiber snack bars that were created. The proportions of purple sweet potato flour to rice crust flour differed across the four snack bar formulas: FI (100%:0%), F2 (90%:10%), F3 (80%:20%), and F4 (70%:30%). The effectiveness index method was employed to determine the optimal formulation for the snack bar. The results indicated that lowering the proportion of purple sweet potato flour would enhance the firmness and color of the snack bar. The dietary fiber content (%db) of each formula was as follows: F1 (18.92 ± 1.43%), F2 (18.33 ± 0.79%), F3 (18.56 ± 2.73%), and F4 (19.48 ± 0.40%). The sensory test results showed a direct correlation between the panelists' preference level and the decrease in the proportion of purple sweet potato flour. Formula F4, consisting of a 70% proportion of purple sweet potato flour and a 30% proportion of rice crust flour, is the optimal formula for creating a snack bar.